Beyond the Evident: an Ecological Analysis of Domestic Violence in Vulnerable Environments - Ivone Brito; Nuria Rodríguez Ávila (Musas, 2024)
Based on the ecological approach, women who have been victims of domestic violence interpret and experience their environment in various ways, identifying individual, family, community, and social factors that contribute to the perpetuation of domestic violence. Objective. Explore the factors linked to domestic violence from the subjective experience of Colombian women. Materials and Methods. The research was based on a thematic analysis involving in-depth interviews with 30 women from the District of Santa Marta, Colombia. These interviews address both the participants’ sociodemographic characteristics and the associated factors, from the perspective of the ecological model of violence in the domestic environment. Results. There are topics associated with domestic violence such as age, socioeconomic stratum, educational level, and economic contributions to the home. In addition, past experiences in the internal armed conflict in Colombia, experiences of violence in the domestic environment, strategies for seeking help from the State, and other relevant factors according to the ecological model. Conclusions. The findings highlight the complexity and interaction between various factors that contribute to the perpetuation of domestic violence, underscoring the need to address it in a comprehensive and multidimensional manner.